(untitled) (International Journal of Banking and Finance, 2022)
This paper reports key findings about currency risk using two samples of listed firms: one sample with zero foreign currency revenues, hence having zero-currency risk; and the other sample with positive revenues in foreign currencies from foreign transactions. The latter is therefore, exposed to currency risk. Asset pricing theories predict that stocks of currency-risk-exposed firms should suffer significant currency risk, while those firms with zero-currency-risk should not have any effect from currency risk since currency transactions across borders is nil. The latter hypothesis has yet to be tested explicitly, so there is a gap in the literature. We report stock returns are significantly affected not just for firms with foreign-currency revenues but also for firms with zero foreign-currency transactions. These findings are useful to top management of all businesses to undertake currency-hedge plans for both domestic and international trading firms.